Control and risk prevention plans in chemical product inventories in Latin America - Silva, Laís Libanori da; Fortunato, Murilo Henrique Tank (Brazilian Journal of Production Engineering, 2026)
Context. The indiscriminate use of chemical substances has caused serious harm to human health and the environment. In this context, the creation and effective management of chemical inventories have become fundamental strategies for governments to align with UN guidelines and the Sustainable Development Goals of the 2030 Agenda, strengthening control and the protection of both the environment and public health. Objective. Thus, this study aimed to identify the impacts and risks faced by organizations regarding the recently implemented chemical inventories in Chile and Colombia. These two countries were chosen as references in the project to assess the risks associated with their national chemical inventories from both governmental and industrial perspectives. Method. The methodology involved a literature review and the application of questionnaires to different stakeholders in order to analyze the effects of the current regulations. Results. Based on the results, the use of the Ishikawa Diagram was proposed to identify the causes of the main problems found, enabling more consistent risk management and the continuous improvement of practices within the evaluated industries and governments. This approach promotes a systematic analysis of causes and contributes to strengthening regulatory management and the chemical sector in the region.